KONSTRUKSI AKU DALAM DIATESIS MEDIAL REFLEKSIF BAHASA INDONESIA PADA NOVEL TERJEMAHAN - Matradewi, Ni Ketut Widhiarcani (Adabiyyāt: Jurnal Bahasa dan Sastra, 2018)
The translation of the pronoun persona “I” on Indonesian translation novels is very dynamic and varied. This is interesting when simple and static forms in French are finally able to be translated into varied and unique forms, without breaking away from the rules of language that apply in Indonesian. This study examines the “I” figure contained in the construction of the medial diathesis of Indonesian which is translated from two French novels: Pendidikan Istri by Apsanti Djokosujatno from l’Ecole des Femmes by Andre Gide and Lara Kusapa by Ken Nadya from Bonjour Tristesse by Francoise Sagan. The critical linguistic approach is chosen in this study to see the ideology behind the “I” construction. From the analysis of this study, it is found that “I” construction is an important strategy carried out by the translators to construct the translators’ ideology in translating reflexive medial diathesis forms. Linguistically, the translations are carried out with positive lexicalisation, adverb addition, idiom use, nominalization, and the substitution of the “I” character with other pronouns when the “I” character is in a predominant position. Extralinguistically, the translations are related to the factors of creativity, ideology, and the context of the target language.